(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Although women are main part as a major labor force at every stage of agricultural activity and undertake responsibilities such as domestic task and childcare, they do not profit from social and economic benefits proportionate to the responsibilities they have undertaken. In particular, women living in rural areas work harder than urban women, that is, they do field work (picking cotton, tending cattle, irrigating the land, or harvesting crops) in addition to housework and are not paid for it. it is known from the world experience that through agritourism, rural women earn income for their work in the field as well as household work. In the article, it is studied from foreign experiences that the employment of women in agritourism has a positive effect on obtaining economic and social benefits.